A strategy for finding new medicines against the novel coronavirus disease (COVID-19) derived from base pairing with DNA damages - Katsuhito Kino; Takayuki Ohshima; Taishu Kawada; Takanobu Kobayashi; Hiroshi Miyazawa (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2020)
The spread of the novel coronavirus disease (COVID-19) has caused a global pandemic. Exiting agents that act on proteins including 3-chymotrypsin-like protease (3CLpro), papain-like protease (PLpro), helicase, RNA-dependent RNA polymerase (RdRp), spike glycoprotein (S protein), and others in similar viruses [1,2] are likely used as antiviral drugs against the novel coronavirus (SARS-CoV-2). Data on Chemical Abstract Service show that the potential drug candidates against 3CLpro and RdRp are more than those against other targets [2].